The devil : a new biography - Almond, Philip C. (Cornell University Press, 2014)
"In The Devil, Philip C. Almond explores the figure of evil incarnate from the first centuries of the Christian era. Along the way, he describes the rise of demonology as an intellectual and theological pursuit, the persecution as witches of women believed to consort with the Devil and his minions, and the decline in the belief in Hell and in angels and demons as corporeal beings as a result of the Enlightenment. Almond shows that the Prince of Darkness remains an irresistible subject in history, religion, art, literature, and culture."--